Phyllanthin Topical Formulation with Penetration Enhancers Alleviates Imiquimod-Induced Psoriasis in Rats via Modulation of Inflammatory Biomarkers and Oxidative Stress Markers - Bigoniya, Papiya; Chature, Vanita (International Journal of Pharmaceutical Investigation, 2026)
Background Psoriasis is a persistent inflammatory skin condition marked by abnormal epidermal proliferation and excessive keratinization, impairing effective drug absorption. To overcome these barriers, topical formulations containing skin permeability enhancers are widely employed to improve drug delivery and therapeutic effectiveness. Materials and Methods Phyllanthin isolated from Phyllanthus acidus leaves was formulated into an ointment alongside permeability enhancers, eucalyptus, basil, and cardamom oils. Psoriasis like symptoms were induced in Wistar rats using Imiquimod (IMQ) to assess the efficacy of phyllanthin ointments on the ear and dorsal skin. Ointment formulations containing 1% and 2% phyllanthin were applied topically once daily at 200 and 400 mg daily for ten days post-induction of psoriasis. The Psoriasis Area and Severity Index (PASI), along with the thickness of the ear, body and relative organ weight, antioxidant and anti-inflammatory markers, and histopathological changes, were all assessed in the study. Results and Discussion The ointments were found to be physically stable up to 37ºC. The 2% phyllanthin ointment, containing 0.5% of each essential oil, produced a profound lowering of PASI score (p<0.01) and ear thickness (p<0.001) in concern to untreated controls. No signs of acute topical toxicity were observed with phyllanthin treatment, and it did not negatively affect body weight or organ weight indices. Phyllanthin significantly increased hydroxyproline, reduced lipid peroxidation, IL-6, TNF-α, (p<0.05-0.001) content, keratinocyte hyperproliferation, and lymphocytic infiltration in the affected tissues. Conclusion Phyllanthin ointment with essential oils effectively alleviated psoriatic symptoms and demonstrated strong antioxidant and anti-inflammatory activity, indicating its potential for once-daily use in managing psoriasis.
Keywords: Inflammation; Penetration Enhancer; Phyllanthin; Phyllanthus acidus; Psoriasis; Topical Formulation.